(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In recent years, with the deepening of curriculum reform and the promulgation of the General High School Biology Curriculum Standards (2017 Edition), it has had a great impact on the previous high school biology education concept. Under these conditions, it is required that front-line teachers must actively explore and discover new teaching models and make practical improvements. Teaching effect. Project-based learning is a teaching model that emphasizes student-centered, problem-solving as the guide, and focuses on students’ all-round ability cultivation. Through project-style study integrating with the teaching of biology courses can effectively improve the current situation of biology teaching, which is of great significance to the improvement of students’ biology literacy and comprehensive literacy. In the study of this article, through project-based learning in high school biology teaching the positive impact on students,Project-based learning content design analysis, clear project-based learning carry out and implement, and then analyze the current situation of high school biology teaching. On this basis, with the help of the project-based learning mode,The impact of project-based learning on students’ comprehensive quality in high school biology teaching make an analysis.